Research on Data Security and Privacy Protection in Corporate Human Resource Management in the Digital Era - Biao Zhang; Zhuoxin Li; Ke Xie; Ting Li; Binbin Huang (Journal of Frontier in Economic and Management Research, 2025)
Against the backdrop of the global digital wave, human resource management (HRM) in innovation and entrepreneurship enterprises is undergoing profound transformation, with data emerging as a core asset driving corporate decision-making and development. However, issues related to data security and privacy protection have become increasingly prominent, serving as key factors restricting the sustainable development of enterprises. By analyzing the challenges faced by innovation and entrepreneurship enterprises in data security and privacy protection within HRM, this paper explores the importance of these issues and proposes countermeasures such as constructing a data security governance system, applying privacy computing technologies, and enhancing employees’ data security awareness. The aim is to provide theoretical references and practical guidance on data security and privacy protection for innovation and entrepreneurship enterprises, helping them achieve a balance between security and development during digital transformation.